Financial development, impact on output and its determinants : the case of the economic community of the West African states - Abubakar, Abdulsalam (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The role of financial development to influence the capital accumulation, productivity and hence economic growth, has continued to take a centre stage in the economic growth literature. The apparent low level of economic performance of the Economic Community of West African States (ECOWAS) region, low physical and human capital accumulations and low productivity have raised issues about the role of financial development to the economic growth process of the region and serve as the motivation of this study. The study investigates the impact of financial development on the output of eleven ECOWAS member states over the period from 1980 to 2011. The determinants of financial development in ECOWAS from 1996 to 2011 period are also examined. The study employs panel cointegration techniques, which involve panel cointegration tests by Pedroni (2000; 2004) and Kao (1999) and two panel cointegration estimators, namely; the fully modified OLS (FMOLS) and dynamic OLS (DOLS). Furthermore, the study adopts the Dumitrescu-Hurlin (2012) panel causality test to determine the causal relationship between financial development and output in ECOWAS. The findings show that broad money and financial sector deposits have negative and significant impact on the output, as found by Hakeem (2010) in sub-Saharan African region. On the other hand, banking sector deposits, domestic credit, bank credit and the ratio of bank credit to bank deposits are found to have positive and significant impact on output in ECOWAS. This is consistent with the findings of Ndebbio (2003) and Gaye (2013). These effects are largely transmitted through the physical capital accumulation channel, as found by Rioja and Valev (2003) in developing countries. The empirical evidence further shows that whereas unidirectional causality runs from GDP to broad money and bank deposits, the reverse is the case for bank credit and ratio of bank credit to bank deposits. Similarly, bidirectional causality is found to exist between financial sector deposit and domestic credit on one hand, and GDP on the other hand. These findings are consistent with that of Bangke and Eggoh (2010). For determinants of financial development, inflation, institutional quality and current account openness are found to be the major determinants of financial depth. While financial intermediation activities are determined by a combination of the previous factors and the level of income and human capital accumulation. These findings largely explain the connection between lack of access to finance by a larger segment of the household and private sectors in the ECOWAS and the low levels of output in the region. Hence, the major policy implications are that financial policies in the region should aim at eliminating and/or mitigating factors that hinder access to finance. These can be achieved through, economic, legal, political and other institutional reforms, which can also enhance financial development in the region and position it to better serve the real economy.